A pneumatic non-explosive quick stop device for CNC turning machine - Amiril Sahab, Abdul Sani; Shahandzir, Baharom (2021)
A pneumatic Quick Stop Device (QSD) is a device to collect chip-root sample during machining process. The device will freeze the chip formation during the machining process. The device will have a mechanism to retract cutting tool during machining process. The frozen chip formed will have minimal changes in its geometrical and metallurgical properties, thus can be used for evaluating the performance of the cutting process especially during lubrication. By analyzing the freeze chip formation, the life expectancy of the tool, amount of friction and heat produced can be acquired.